Quantifying Journalism? A Study on the Use of Data and Gamification to Motivate Journalists. (December 2017) - Ferrer-Conill, Raul
According to previous research, contemporary journalism is undergoing a quantitative turn. The uses of data and metrics have started to permeate digital news websites in various ways. However, there is a lack of research on how gamification is applied to journalism practice. This article examines how the quantification of news production, readers' interactions, and use of game mechanics have started to permeate journalism practice in digital outlets. Methodologically, this article focuses on the sports news website Bleacher Report as case study, drawing data from an analysis of the gamified system in which journalists are quantified and rewarded with points and badges according to their writing metrics, and a set of interviews with journalists who work for Bleacher Report. The results show that while data and metrics become the main component to assess journalists' capacities, the process of automated quantification and the competitive playfulness of leaderboards are perceived as motivating affordances.